Countering violent extremism: a realist review for assessing what works, for whom, in what circumstances, and how? - Gielen, Amy-Jane (Terrorism and political violence, 2019)
Scientific knowledge on what works in countering violent extremism remains limited. This article argues that we should move away from the “what works?” question and towards: “what works, for whom, in what circumstances, and how?” This method is also known as realist evaluation. This article applies the realist review method to CVE studies, which synthesizes the existing CVE literature and helps us gain insight into relevant contexts, mechanisms, and outcomes for CVE. Realist reviews help to develop and shape more effective policy and contribute to further CVE theory development.